Basic Values and Morality Islamic Education Leadership - Mutholib Mutholib (Al-Hayat Al-Istiqomah Foundation, 2018)
A good leader is always associated with the success of a school that is led. There is a significant correlation between school performance and effectiveness. A leader in an Islamic education institution must have the ability to regulate, influence and direct must be based on the values and leadership ethics governed in the Qur'an and al-hadith. An effective leader always has a clear vision, which is then implemented into a clear work program. To be a good leader must have a social mission about the school, which will be a factor influencing the effectiveness of leadership, then become a necessity to explore the success competence of an educational institution. Principals who maintain good ethics and morality will create a conducive and comfortable school climate, then these conditions will support the creation of effective and efficient learning conditions.Pemimpin yang baik selalu berhubungan dengan keberhasilan sekolah yang dipimpin. Ada korelasi yang signifikan antara kinerja sekolah dan efektifitas. Seorang pemimpin dalam lembaga pendidikan Islam harus memiliki kemampuan mengatur, mempengaruhi dan mengarahkan harus didasarkan pada nilai dan etika kepemimpinan yang diatur dalam al-qur'an dan al-hadits. Seorang pemimpin yang efektif selalu memiliki visi yang jelas, yang kemudian di implementasikan ke dalam program kerja yang jelas pula. Untuk menjadi pemimpin yang baik harus memiliki misi sosial tentang sekolah, yang akan menjadi faktor berpengaruh terhadap efektifitas kepemimpinan, kemudian menjadi suatu keharusan menggali kompetensi keberhasilan sebuah lembaga pendidikan. Kepala sekolah yang menjaga etika dan moralitas yang baik akan menciptakan iklim sekolah yang kondusif dan nyaman, selanjutnya keadaan seperti ini akan menunjang terciptanya kondisi pembelajaran yang efektif dan efisien.